The marketer's guide to public relations in the 21st century - Thomas L. Harris (Texere, 2006)
This book is a complete update of an earlier volume that Harris wrote in 1993. The entire concept of The Marketer's Guide to Public Relations runs counter to the traditional concept of 'events-driven' public relations. This book challenges the reader to use public relations as a strategic tool, to achieve measurable and actionable marketing objectives. Not dissimilar to the concept of 'Integrated Marketing Communications', MPR seeks to read one's market, determine need, and build a marketing program (both communciation and marketing strategy) from the outside in: determine the way customers want to learn about your product and develop a strategy to create awareness, communcate the benefits, and instill a motivation to purchase